Socio-economic profile of the students of Notre Dame of Matalam, SY 1984-1985 - Juloya, Jesus A. (Animo Repository, 1985)
v. 1. This study determines the socio-economic profile of the students of Notre Dame of Matalam. The study used the descriptive method of research. The subjects of the study were 283 students who were selected by stratified sampling from the total population of Notre Dame of Matalam during the school year 1984-1985 using year level as the stratum. To determine the socio-economic profile of the students, the study adopted the PAASCU socio-economic survey questionnaire. Some questions that seemed not applicable to the respondents were changed, others were not included and some were modified. Personal interviews with the school administrators, faculty, students and parents were also conducted to aid in the analysis and interpretation of data. The percentage values were computed in each year level and the total number of responses by the students. A conversion table and rating plan to determine the socio-economic level of the respondents was adopted and modified based on previous researches and Hunt's classification of social classes in the Philippines. Based on the findings of the study, it was concluded that majority of the students of Notre Dame of Matalam belonged to the low socio-economic status according to the norms used. Majority of the students' families were low income earners, hence, the school would have difficulty in increasing tuition fees. The socio-economic profile of the students provided vital information to the school administrators in policy-making and future development plan. The information gathered in this study provided faculty members and guidance counsellors additional information regarding the students' family background which were vital in lesson planning and counselling. v. 2. This study analyzes the financial viability of Notre Dame of Matalam from school year 1985-86 to 1987-88. The study employed a descriptive method of research which involved the analysis of enrollment trends for the last five years, 1980-81 to 1983-85 and the financial status for last three years, 1982-83 to 1984-85 at Notre Dame of Matalam. Based on the analysis of data, a three-year enrollment projection and financial forecast was formulated for the school year 1985-86 to 1987-88.Data were obtained from the school enrollment records, school financial records and the audited financial statements of the school. Interviews with the administrators, registrar, cashier, bookkeeper, faculty and students were also conducted to gather information on the present condition of the school. Findings of the study showed that the trend of enrollment had been increasing from the school year 1980-81 to 1982-83 and decreasing from school year 1983-84 to 1984-85. The school had not been viable for the last three years from school year 1982-83. It depended on financial aid from the bishop. It was found that the total enrolment will decrease, the income of the school will decline and the school will not be financially viable in the next three years.